Ozone therapy versus surgery for lumbar disc herniation: A randomized double-blind controlled trial - Bernardino Clavo; Francisco Robaina; Gerard Urrutia; Sara Bisshopp; Yolanda Ramallo; Adam Szolna; Miguel A. Caramés; María D. Fiuza; Renata Linertová (Elsevier, 2021)
Objectives: Surgery is the treatment of choice for symptomatic disc herniation after conservative management. Several studies have suggested the potential utility of intradiscal ozone infiltration in this pathology. The aim of this trial was to compare intradiscal ozone infiltration vs. oxygen infiltration vs. surgery. Design and interventions: This was a randomized, double-blinded, and controlled trial in patients on a waiting list for herniated disc surgery. There were three treatment groups: surgery; intradiscal ozone infiltration (plus foraminal infiltration of ozone, steroids, and anesthetic); intradiscal oxygen infiltration (plus foraminal infiltration of oxygen, steroids, and anesthetic). Main outcome measures: The requirements for surgery. Results: Five years after the treatment of the last recruited patient (median follow-up: 78 months), the requirement for further surgery was 20 % for patients in the ozone group and 60 % for patients in the oxygen group. 11 % of patients initially treated with surgery also required a second surgery. Compared to the surgery group, the ozone group showed: 1) significantly lower number of inpatient days: median 3 days (interquartile range: 3-3.5 days) vs. 0 days (interquartile range: 0-1.5 days), p =  0.012; 2) significantly lower costs: median EUR 3702 (interquartile range: EUR 3283-7630) vs. EUR 364 (interquartile range: EUR 364-2536), p =  0.029. Conclusions: Our truncated trial showed that intradiscal ozone infiltrations decreased the requirements for conventional surgery, resulting in decreased hospitalization durations and associated costs. These findings and their magnitude are of interest to patients and health services providers. Further validation is ongoing.